Pengaruh Inklusi Keuangan terhadap Kemiskinan di 33 Provinsi di Indonesia - Raden Rizal Rukanda (Jurusan Ilmu Ekonomi Universitas Katolik Parahyangan, 2023)
Financial inclusion is believed to be one way to reduce poverty. Financial inclusion can provide opportunities for poor or marginal social groups in order to improve their lives with the availability and ease to be able to use the formal financial services are affordable and low cost. This study uses the ratio of the number of banking offices per 100 thousand of the adult population, the ratio of the number of credits per the GRDP, and the ratio of the number of third-party funds per GRDP to describe financial inclusion in terms of access and use of financial services. The data used is panel data of 33 provinces annually for the period 2011 to 2019 processed with static panel data regression. The results show that financial inclusion by increasing the use of banking products such as savings, current accounts and time deposits can reduce poverty in Indonesia.